Development of Prompting Questions, Reading On The Lines, Reading In The Lines, and Reading Beyond The Lines in Strengthening Reading Literacy of Grade IV Elementary School Students - Aini, Muntaza Nur; Nurchasanah, Nurchasanah; Kusumaningrum, Shirly Rizki (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to develop prompting questions used to strengthen the reading literacy of fourth-grade elementary school students that are valid, practical and effective. The development model used in this research is the ADDIE model which consists of five development stages, namely Analyze, Design, Development, Implementation, and Evaluation. The test subjects in this research were reading literacy experts, class teachers, and fourth-grade elementary school students. The research data consists of validation data on reading literacy, practicality of teacher users, and student effectiveness. The expert validation results obtained a value of 90%. The results of the effectiveness test on students obtained a result of 0.601 for the small group and a result for the large group of 0.707. Apart from that, the results were also obtained from the practicality of teacher users of 100%. Based on these results, it can be concluded that the development of leading questions is valid, practical and effective.